The use of coffee (Coffea arabica L.) pulp in the preparation of a beverage with antioxidant properties - Uscanga Sosa, D. P. (2024)
The main by-product of the coffee industry is the fruit pulp. Therefore, finding alternatives for its use is crucial to avoid water and environmental pollution, since the residue contains high amount of organic matter. The aim of the present work was to evaluate the use of coffee pulp in the formulation of a beverage (tisane). Tisanes were formulated by combining coffee pulp, blueberry and strawberry, based on the levels of a rotatable central composite design. Eighteen combinations were evaluated by specialised coffee tasters, and the two best formulations (6 and 14) were selected. These two formulations were then sensory-evaluated by 100 consumers in terms of appearance, colour, aroma, body, sweetness, and flavour. Most consumers enjoyed both formulations, with formulation 14 (3.75 g coffee pulp, 3.75 g blueberry, and 5.75 g strawberry) received higher preference of 92%, 87% would buy it if it became available on the market, and 99% would buy it if it had health benefit. Based on chemical and nutritional analyses, formulation 6 yielded 26.95 mg GAE/g of total phenolic compounds, and 9,110.65 µmol Trolox/g of antioxidant activity. These indicated that the formulated beverage had high antioxidant capacity as well as high consumer acceptance.